2017
DOI: 10.1038/nrn.2017.107
|View full text |Cite
|
Sign up to set email alerts
|

The use of brain organoids to investigate neural development and disease

Abstract: Understanding the development and dysfunction of the human brain is a major goal of neurobiology. Much of our current understanding of human brain development has been derived from the examination of post-mortem and pathological specimens, bolstered by observations of developing non-human primates and experimental studies focused largely on mouse models. However, these tissue specimens and model systems cannot fully capture the unique and dynamic features of human brain development. Recent advances in stem cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
490
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 590 publications
(529 citation statements)
references
References 91 publications
4
490
1
Order By: Relevance
“…This could be due to the largely absent bRG population in the developing mouse neocortex. It may be useful to utilize in vitro models of human cortical development such as human cerebral organoids formed from patient-derived induced pluripotent stem (IPS) cells [95]. Furthermore, whether variations in Shh signaling activity during corticogenesis affect maturation and connectivity of upper layer PNs produced by IPs and bRGs should be investigated.…”
Section: Implications Of Shh Signaling In Neurological Disordersmentioning
confidence: 99%
“…This could be due to the largely absent bRG population in the developing mouse neocortex. It may be useful to utilize in vitro models of human cortical development such as human cerebral organoids formed from patient-derived induced pluripotent stem (IPS) cells [95]. Furthermore, whether variations in Shh signaling activity during corticogenesis affect maturation and connectivity of upper layer PNs produced by IPs and bRGs should be investigated.…”
Section: Implications Of Shh Signaling In Neurological Disordersmentioning
confidence: 99%
“…The small effect sizes may still be a problem, but others and we have shown that when one works with modified or edited cells, small effect variants can lead to robust cellular phenotypes [103, 105, 139, 176]. These technologies are new, and there is still much space for improvement, including editing efficiency [177], uniform and specific differentiation [178, 179], the time needed for maturation, and the faithful recapitulation of cortical circuits by organoids [180]. Nevertheless, the genetic findings are there and the tools for us to understand them are rapidly evolving, giving hope for significant breakthroughs within the next decade.…”
Section: Closing Remarksmentioning
confidence: 99%
“…They allow interpretation of whether genetic variants associated with neuropsychiatric illness are also associated with the structure or function of the human brain within specific regions. Finally, directed stem cell differentiation protocols producing specific cell types from multiple brain regions and modern genetic engineering techniques allow the experimental validation of predicted causal pathways in a controlled human system . This review seeks to place maps of genetic variation associated with gross brain structure into context and explain their utility for describing causal pathways impacting risk for neuropsychiatric disorders.…”
Section: The Role That Human Neuroimaging Of Gross Brain Structure Camentioning
confidence: 99%